The Nazi officer's wife how one Jewish woman survived the Holocaust - Beer, Edith Hahn; Dworkin, Susan ([New York] Perennial, 2000)
Edith Hahn tells how she survived the Holocaust, first by going underground, using a Christian friend's identity papers, and eventually marrying Werner Vetter, a Nazi Party member who knew she was Jewish.
Keywords: Beer, Edith Hahn; Jews -- Austria -- Vienna -- Biography; Holocaust, Jewish (1939-1945) -- Austria -- Vienna -- Personal narratives; Vienna (Austria) -- Biography; Electronic books